Syllabus for Race, Performance, and Media Studies - Petty, Miriam J.; Chambers-Letson, Joshua (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
A reflection on the serious work and pressing exigencies of interdisciplinary teaching at the intersection of media studies, performance studies, and race and ethnic studies, this syllabus is both a portrait of pandemic pedagogy and a reflection of the work of friendship and mutual struggle.